2009
DOI: 10.1016/j.febslet.2009.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expressed microRNA‐27a and 27b influence fat accumulation and cell proliferation during rat hepatic stellate cell activation

Abstract: Retinoid X receptor aLiver fibrosis a b s t r a c t Hepatic stellate cells (HSCs) activation is an initial event in liver fibrosis. MicroRNAs (miRNAs) have been found to play essential roles in cell differentiation, proliferation, and fat metabolism. In this study, we showed that down-regulation of two over-expressed miRNAs, miR-27a and 27b allowed culture-activated rat HSCs to switch to a more quiescent HSC phenotype, with restored cytoplasmic lipid droplets and decreased cell proliferation. Mechanistically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
179
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(200 citation statements)
references
References 25 publications
17
179
3
1
Order By: Relevance
“…5 Emerging evidence has revealed that miRNAs are implicated in HSC activation and thereby regulate liver fibrosis. [6][7][8][9] For example, Wang et al reported that miR-29b prevents liver fibrosis by suppressing HSC activation and inducing cell apoptosis via targeting PI3K/ AKT pathway. 3 Our previous study found that curcumin upregulates miR-29b expression, leading to the silencing of DNA methyltransferase 3b (DNMT3b) and the loss of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) methylation, which contributes to suppression of activated HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Emerging evidence has revealed that miRNAs are implicated in HSC activation and thereby regulate liver fibrosis. [6][7][8][9] For example, Wang et al reported that miR-29b prevents liver fibrosis by suppressing HSC activation and inducing cell apoptosis via targeting PI3K/ AKT pathway. 3 Our previous study found that curcumin upregulates miR-29b expression, leading to the silencing of DNA methyltransferase 3b (DNMT3b) and the loss of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) methylation, which contributes to suppression of activated HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the percentage of cells in G 2 -M was consequently increased. Other studies also found that the suppression of miR-27a can inhibit gastric cancer cell growth [57] and overexpression of miR-27a increases the fat accumulation and cell proliferation of Hepatic stellate cells [58]. Therefore, miR-27a is considered as an oncogene.…”
Section: Discussionmentioning
confidence: 96%
“…However, we did not observe any effect of RBV treatment in OR6Ac cells (data not shown). The RXRα protein level is known to be regulated by microRNAs (miRNAs), such as miR‐27a40, 41 and miR‐34a,42 suggesting that these miRNAs may regulate RXRα expression in hepatic cells treated with RBV.…”
Section: Discussionmentioning
confidence: 99%